Part A: Design of new camphor-based hydrazide organocatalysts and their applications to enantioselective Friedel-Crafts alkylations Part B: The development of the palladium catalyzed addition of organoborates to alkynyl esters: Synthesis of trisubstituted olefins as single isomers - Bush, Alexander Graham (University of Ottawa (Canada), 2009)
Part A. Asymmetric synthesis is a growing field in synthetic and medicinal chemistry. Investigations into the use of organocatalysts to engender chirality into organic molecules is of particular interest. Herein we present the study of the efficiency of camphor-based hydrazide organocatalysts in the asymmetric Friedel-Crafts alkylations of N-methylindole with alpha,beta-unsaturated aldehydes. In addition, the applicability of newly designed second-generation camphor-based hydrazide catalysts will be examined.* Part B. The synthesis of trisubstituted olefins represents an intriguing target in organic chemistry. However, the stereocontrolled synthesis of trisubstituted olefins can prove to be difficult, as mixtures of isomers are often obtained. A new methodology is presented herein that allows for the synthesis of single isomer trisubstituted olefins by a palladium catalyzed reaction of alkynyl esters with aryl and vinyl boronic acids under mild reaction conditions by using the simple phosphine ligand Et3P. The process provides alpha,beta-unsaturated esters with complete control of the stereochemistry and regiochemistry at the newly formed the double bond.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Organic.